ICT outsourcing from Malaysia public sector perspective / Sallehuddin Affandi - Affandi, Sallehuddin (2006)
Governments have worked together with non-governmental entities to deliver public services to citizens as well as for developing and operating internal management systems. Much attention has been given to the computerization of government ministries and agencies to improve the government's capacity to carry out its tasks and cope with the future challenges in order to achieve performance goals. The aims of this research are to identify the motivation to information communication and technology (ICT) outsourcing, to determine the ICT services that are currently being outsourced and to describe the risks inherent in ICT outsourcing from Malaysian public sector perspective. In order to achieve the aims of this research, an expanded research model was used to develop the research instrument for this study. The primary data for this research was collected by means of a questionnaire survey conducted among Malaysian public sector organizations. There are about 50 federal government agencies based in Putrajaya. Out of that, 28 federal government agencies and 12 state federal government agencies (within Klang Valley) were selected to participate in the survey. A total of 250 questiormaires were distributed among the selected organizations and within one and half months, about 190 completed questionnaires were returned. Although the research was conducted successfully, several limitations were encountered. The limitations are time constraint, limited academic reference on ICT outsourcing based in Malaysia and lack of cooperation during field study. The findings from this research indicated some ICT services that are currently being outsourced in the Malaysian public sector. Some motivation factors and risks inherent in ICT outsourcing were also reported.